Air-Core Non-Zero Dispersion-Shifted Fiber With High-Index Ring for OAM Mode - Wenqian Zhao; Wenpu Geng; Yingning Wang; Yuxi Fang; Changjing Bao; Yongxiong Ren; Weigang Zhang; Hao Zhang; Zhongqi Pan; Yang Yue (IEEE Access, 2021)
It is well-known now that orbital angular momentum (OAM) modes can be a potential technology to take full advantages of the space resources in the fiber-based optical communication system because of its infinite states. However, the corresponding fiber design for OAM modes to meet various requirements in the fiber-based communication system is still not enough. For the dispersion property, there are various attributes given in the standard of ITU-T series, which has not yet been proposed for the OAM modes. In this paper, we propose and design a non-zero dispersion-shifted air-core ring fiber for OAM mode, which can offer more options on dispersion values. A negative dispersion of −1.246 ps/(nm $· $ km) or a positive dispersion of 1.541 ps/(nm $· $ km) at 1550 nm with < 1.5 ps/(nm $· $ km) dispersion variation across the C band or < 4 ps/(nm $· $ km) dispersion variation across the C and L bands for OAM $_{1,1}$ mode is achieved in the numerical simulation.